Simultaneous quantification of davalintide, a novel amylin-mimetic peptide, and its active metabolite in beagle and rat plasma by online SPE and LC–MS/MS. (September 2012) - Wang, Yan; Qu, Ying; Bellows, Chris L; Ahn, John S; Burkey, Jennifer L; Taylor, Steven W
Background: Davalintide, an investigational therapeutic peptide for the treatment of obesity, is rapidly metabolized by enzymatic cleavage of its N-terminal lysine residue to produce an active des-Lys metabolite in vivo . While a sensitive ELISA assay is available, it is unable to distinguish davalintide from its metabolite. Consequently, we developed an online SPE–LC–MS/MS method for simultaneous quantification of the drug and its active metabolite in beagle and rat plasma samples and compared the resulting pharmacokinetic profiles with those determined by ELISA.Results: The total concentration of active drug measured by ELISA correlated well with the total concentration of davalintide and its metabolite using online SPE–LC–MS/MS.Conclusion: The technique is a viable alternative to immunochemistry-based methods for peptide quantitation in terms of sensitivity, reproducibility and specificity, and importantly, does not require developing antibody-based reagents.